PENDAMPINGAN KEPALA SEKOLAH DALAM IMPLEMENTASI KURIKULUM MERDEKA - Cicih Sutarsih; Udin Syaefudin Saud (Jurnal Pasca Dharma Pengabdian Masyarakat, 2022)
The principal's assistance to teachers can be identified from two sides, namely: organizational resource capacity and organizational management capacity. This community service is carried out with the aim of implementing the mentoring model carried out by elementary school principals in implementing the independent curriculum and identifying the competencies and skills of school principals which are the determinants of the principal's mentoring model. The results of Community Service obtained are the mapping of an effective model in the process of assisting school principals in the implementation of the independent curriculum and recommendations for guidance on the readiness of school principals in assisting teachers.